PENGARUH UKURAN PERUSAHAAN DAN RISIKO GAGAL BAYAR PADA KOEFISIEN RESPON LABA - Kartika Rahayu, L.P. Agustina; Suaryana, I.G.N Agung (E-Jurnal Akuntansi; Vol 13 No 2 (2015), 2015)
The purpose of this study was to determine the effect of the size of the company and the risk of default on laba.Penelitian response coefficients is performed on companies listed in Indonesia Stock Exchange 2009-2013 period . Samples was determined using nonprobability sampling method is purposive sampling . The number of samples selected were 36 companies . Data analysis method used is linear regression analysis berganda.Berdasarkan analysis has been done , this study proves that the positive effect of firm size on earnings response coefficients . While the default risk of negative impact on earnings response coefficients .
Keywords: Firm Size, Default Risk , cumulative abnormal return , Earnings Surprises , Earnings Response Coefficient